Spectroscopic evidence for conformational relaxation in myoglobin. - Nienhaus, G U (1992)
The time and temperature dependencies of the line area (M0) and position (M1) of band III at approximately 760 nm have been measured with Fourier-transform infrared spectroscopy in deoxymyoglobin (Mb) and continuously photolyzed carbon monoxide myoglobin (MbCO). Below 200 K, the area of band III in the photoproduct Mb* increases with time even on time scales of hours. This behavior indicates changes in the distribution of activation enthalpy barriers for ligand rebinding under extended illumination. The band position of Mb* shifts to higher wavenumbers with increasing temperature up to 100 K owing to kinetic hole burning; the same protein coordinate that controls the position of band III also determines the rebinding barrier height. The shift ceases above 100 K, implying that more than one protein coordinate affects the height of the rebinding barrier. Above 160 K, the line position in Mb* shifts again and coalesces with the value of Mb for temperatures above 200 K. The shift is accompanied by an increase of the line area, reflecting a slowing of rebinding kinetics. Both effects are explained in the framework of the model introduced by Steinbach et al. [(1991) Biochemistry 30, 3988-4001]. Above approximately 160 K, the conformational relaxation Mb*----Mb simultaneously shifts the line position of band III and increases the enthalpy barrier for ligand rebinding. Furthermore, equilibrium fluctuations lead to an averaging of the band position and the rebinding enthalpy.